Ellipticine increases the superhelical density of intracellular SV40 DNA by intercalation. - Chu, Y (1992)
We investigated the in vivo effect of ellipticine, a mammalian topoisomeraseII(topoII) inhibitor, on SV40 DNA topology. In contrast to epipodophyllotoxins, ellipticine did not cause significant double stranded cleavage of intracellular SV40 DNA. Furthermore, ellipticine reduced cleavage induced by epipodophyllotoxins, VP16 and VM26. Unexpectedly, ellipticine dramatically increased the superhelical density of a fraction of intracellular SV40 DNA. Several lines of evidence suggest that the formation of this highly supercoiled DNA species (Ih form DNA) is not due to the inhibition of topoII per se, but is the result of intercalation by ellipticine in a subfraction of the intracellular SV40 chromatin followed by the fixation of DNA linking number by a topoisomerase activity. Based on the linking number change and the known unwinding angle of ellipticine, the intercalation density was calculated as one ellipticine molecule per 10-20 bp in the Ih DNA. This result suggests the existence of different populations of intracellular SV40 chromatin with respect to the accessibility to ellipticine intercalation.